Effect of Purified Lipopolysaccharides from Strains of Helicobacter pylori and Helicobacter felis on Acid Secretion in Mouse Gastric Glands In Vitro - Padol, Ireneusz T. (American Society for Microbiology, 2001)
As a bacterial product, Helicobacter pylori lipopolysaccharide (LPS) can originate in close proximity to parietal cells, but the role of this uniquely structured endotoxin on acid secretion has not been fully investigated and remains unclear. The purpose of this study was to test the direct effect of purified LPS (tested range, 0.1 to 100 μg/ml) from various strains of H. pylori and from one Helicobacter felis strain on histamine- and carbachol-stimulated acid secretion in vitro using mouse gastric glands and the accumulation of [(14)C]aminopyrine. In addition, we investigated whether H. pylori LPS can interfere with two native antisecretory substances, prostaglandin E(2) (PGE(2)) and somatostatin, which may contribute to bacterial pathogenicity. Except for the LPS from H. pylori SS1 (Sydney strain), which gave a statistically significant increase in both histamine- and carbachol-stimulated acid output (38 and 24%, respectively; P < 0.05), no effect of the tested LPS was observed on acid secretion. H. pylori LPS purified from a patient isolate did not affect the potency or the efficacy of the inhibitory dose response curve to PGE(2) or somatostatin. Bacterial interstrain variation in the direct stimulatory effect of Helicobacter-derived LPS on acid secretion was observed, which probably reflects the molecular structure of LPS and the potential to contribute to virulence. Importantly, the data showed that H. pylori LPS did not have any direct antisecretory properties. It can be speculated that the acid stimulatory properties of LPS from H. pylori SS1 may contribute to the gastric damage observed in the mouse model of H. pylori infection.